CuCN-Mediated cascade cyclization of 4-(2-bromophenyl)-2-butenoates: a high-yield synthesis of substituted naphthalene amino esters - Reddy, R. Santhosh; Prasad, Pragati K.; Ahuja, Brij Bhushan; Sudalai, Arumugam (Journal of Organic Chemistry, 2013)
A new method of CuCN-mediated one-pot cyclization of 4-(2-bromophenyl)-2-butenoates leading to efficient synthesis of substituted naphthalene amino esters including phenanthrene aromatic structural units is described. Deuterium labeling studies establish that this one-pot cascade cyclization proceeds through isomerization of olefin, intramolecular C-C bond cyclization, and aromatization as the key intermediates, all occurring in a single step.

Copper(I) bromide-catalyzed carbonylative coupling of aryl halides with phenols, alcohols and amines using sodium cyanide as C-1 source: a synthesis of carboxylic acid derivatives - Prasad, Pragati K.; Sudalai, Arumugam (Advanced Synthesis & Catalysis, 2014)
A new ``carbon monoxide-free'' synthesis of carboxylate derivatives via carbonylative coupling of aryl bromides with phenols, alcohols, amines and acids in the presence of copper(I) bromide as catalyst and sodium cyanide in a stoichiometric amount has been developed. Its intramolecular version provides for the preparation of lactones (e.g., isochroman-1-ones and isobenzfuranones), imides, anhydrides and lactams in excellent yields (73-96%).
Keywords: anhydrides; C-1 building blocks; isochroman-1-ones; lactams; lactones

I-2-catalyzed regioselective Oxo- and hydroxy-acyloxylation of alkenes and enol ethers: a facile access to alpha-acyloxyketones, esters, and diol derivatives - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Organic Letters, 2014)
I-2-catalyzed oxo-acyloxylation of alkenes and enol ethers with carboxylic acids providing for the high yield synthesis of a-acyloxyketones and esters is described. This unprecedented regioselective oxidative process employs TBHP and Et3N in stoichiometric amounts under metal-free conditions in DMSO as solvent. Additionally, I-2-catalysis allows the direct hydroxy-acyloxylation of alkenes with the sequential addition of BH3 center dot SMe2 leading to monoprotected diol derivatives in excellent yields.

N-Heterocyclic carbene catalyzed oxidative coupling of alkenes/alpha-bromoacetophenones with aldehydes: a facile entry to alpha,beta-epoxy ketones - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Angewandte Chemie-International Edition, 2015)
{A novel, N-heterocyclic carbene (NHC) catalyzed direct oxidative coupling of styrenes with aldehydes has been described for the synthesis of alpha,beta-epoxy ketones in good yields. This unprecedented regioselective oxidative coupling employs NBS/DBU/DMSO (DBU = 1,8-diazabicyclo [5.4. 0] undec-7-ene
Keywords: aldehydes; epoxidation; N-heterocyclic carbenes; Oxidation; synthetic methods

I-2-mediated regioselective C-3 azidation of indoles - Prasad, Pragati K.; Kalshetti, Rupali G.; Reddi, Rambabu N.; Kamble, Sanjay P.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2016)
An unprecedented synthesis of novel 3-azido indoles has been developed using I-2 and NaN3 in high yields and excellent regio-selectivity. The reaction proceeds under metal-free conditions at room temperature. Essentially, an umpolung in reactivity at the C-3 position of indole has been achieved by the activation of indoles with I-2.

N-heterocyclic-carbene-catalyzed regioselective oxidative ring-opening of epoxides with aromatic aldehydes: a facile entry to alpha-acyloxyketones - Reddi, Rambabu N.; Gontala, Arjun; Prasad, Pragati K.; Sudalai, Arumugam (Asian Journal of Organic Chemistry, 2016)
A high-yielding synthesis of -acyloxyketones using a N-heterocyclic-carbene (NHC)-catalyzed, oxidative ring-opening of epoxides with aromatic aldehydes is described. This regioselective, oxidative process utilizes a N-bromosuccinimide (NBS)/DMSO combination as the oxidant system and Et3N as the base under mild reaction conditions.
Keywords: aldehydes; epoxides; halogen oxidants; N-heterocyclic carbenes; oxygen

Regioselective oxo-amination of alkenes and enol ethers with N-bromosuccinimide-dimethyl sulfoxide combination: a facile synthesis of alpha-amino-ketones and esters - Prasad, Pragati K.; Reddi, Rambabu N.; Sudalai, Arumugam (Organic Letters, 2016)
An unprecedented conversion of alkenes and enol ethers to the corresponding a-imido carbonyl compounds with excellent regioselectivity and yields has been developed. This oxo-amination process employs readily available N-bromosuccinimide (NBS) and secondary amines as N-sources and dimethyl sulfoxide (DMSO) as the oxidant and also leads to the production of amino alcohols in a single step on reduction, thus broadening the scope of this operationally simple reaction. For the first time, the formation of reactive Me2S+-O-Br species generated by the interaction of NBS with DMSO has been proven.

Concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol using Co(III)(salen)-catalyzed hydrolytic kinetic resolution of a two-stereocentered anti-azido epoxide - Reddi, Rambabu N.; Prasad, Pragati K.; Kalshetti, Rupali G.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2017)
A concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol, (+)-DAB-1, has been described in good overall yield (18.1%) and with high enantiomeric purity (up to 98% ee) starting from a simple raw material, cis-2-butene-1,4-diol. The Co-catalyzed hydrolytic kinetic resolution of a two-stereocentered racemic azido epoxide followed by asymmetric dihydroxylation of the alkene and 'one pot' reductive cyclisation of the azido diol are key reactions in the synthetic sequence. (C) 2016 Elsevier Ltd. All rights reserved.